ADAPTATION TRAINING FOR MENTAL RESILIENCE OF ADOLESCENTS USING THE ROY ADAPTATION MODEL APPROACH - Arif Budiman, M. Elyas; Yuhbaba, Zidni Nuris; Erdah Suswati, Wahyi Sholehah; Basri, Achmad Ali (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2024)
Introduction: Adolescence is a key period for mental health, as over half of mental health problems begin during this stage and often persist into adulthood. Many adolescents, however, lack access to specialized care. This research aims to examine the impact of adaptation training on mental health resilience in adolescents, utilizing the Roy Adaptation Model. Method: This quasi-experimental study followed a pre-test-post-test control group design. The sample consisted of 100 adolescents, divided into an experimental group (50 respondents) and a control group (50 respondents), selected using purposive sampling. The experimental group participated in six weeks of adaptation training, with one session held each week. The training aimed to help adolescents better adapt to stressors, fostering mental resilience. The Adolescent Resilience Questionnaire (ARQ) was used to measure resilience, specifically evaluating the capacity to achieve positive outcomes despite facing challenges. The Wilcoxon Paired test was applied to assess differences within each group before and after the intervention, and the Mann-Whitney test was used to compare outcomes between the two groups. Both tests utilized an ordinal scale for analysis. Results: The Mann-Whitney test results showed a significant difference between the experimental and control groups, with a p-value of 0.000. This indicates that adaptation training had a positive effect on increasing adolescent mental resilience. Conclusion: Adaptation training is effective in improving adolescents' mental resilience. It has the potential to be integrated into school programs to support mental health promotion and prevention, offering a proactive approach to addressing adolescent mental health challenges.